(untitled) (Al-Farooq Journal of Sciences, 2026)
This empirical study aims to examine the practices of time management and their direct impact on enhancing job performance among employees at the Hatif Libya Company (Kufra). Utilizing a descriptive-analytical approach, a comprehensive census was conducted covering the entire study population of 22 employees through a structured questionnaire. The collected data were processed using non-parametric statistical methods, primarily Spearman’s rank correlation coefficient. The findings reveal that time management practices are overall at a moderate level; while employees demonstrate strong individual awareness regarding daily planning and prioritization, the organizational environment faces challenges marked by frequent work interruptions and minimal reliance on digital task-scheduling tools. Conversely, overall job performance recorded a high level in terms of task completion and service quality; however, maintaining this performance often incurs high psychological pressure and occupational fatigue due to mitigating time distractions through extra effort. Furthermore, the statistical analysis confirms a significant positive correlation between time management and job performance. Based on these outcomes, the study recommends automating routine procedures, restructuring the customer reception area to isolate public counters from technical offices, and providing targeted training in delegation and time-planning skills.